Applicability of Hooke’s and Jeeves Direct Search S olution Method to Metal cutting [Turning] Operation. - Mr. G. S. Kirgat ,; Prof. A. N. Surade , (International Journal of Innovations in Engineering Research and Technology, 2021)
Role of optimization in engineering design is prominent one with theadvent of computers. Optimization hasbecome a part of computer aided design activities. It is primarily being used in those design activities in which thegoal is not only to achieve just a feasible design, but also a design objective. In most engineering design activities,the design objective could be simply to minimize the cost of productionor to maximize the efficiency of theproduction. An optimization algorithm is a procedure which is executed iteratively by comparing various solutionstill the optimum or a satisfactory solution is found. In many industrial design activities, optimization is achievedindirectly by comparing a few chosen design solutions and accepting the best solution. This simplistic approachnever guarantees and optimization algorithms being with one or more design solutions supplied by the user andthen iteratively check new design the true optimum solution. There are two distinct types of optimizationalgorithms which are in use today.